2004
DOI: 10.1002/mds.20035
|View full text |Cite
|
Sign up to set email alerts
|

Semiquantitative study of current coffee, caffeine, and ethanol intake in essential tremor cases and controls

Abstract: There are several reasons to study caffeine, coffee, and ethanol intake in essential tremor (ET) patients. ET patients also might modify their use of these beverages because of their effects on tremor. Intake of caffeine, coffee, and ethanol has not been quantified in a group of ET patients. Our objective is to use a semiquantitative food frequency questionnaire to compare current daily intake of coffee, caffeine, and ethanol in ET patients and controls. A total of 130 ET cases were patients at the Neurologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 23 publications
3
24
0
Order By: Relevance
“…As reported previously, 41 patients with ET consumed less caffeine than did controls, which is likely to be a dietary modification in response to tremor. The intake of ethanol did not differ between patients with ET and controls.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…As reported previously, 41 patients with ET consumed less caffeine than did controls, which is likely to be a dietary modification in response to tremor. The intake of ethanol did not differ between patients with ET and controls.…”
Section: Discussionsupporting
confidence: 69%
“…The intake of ethanol did not differ between patients with ET and controls. As noted previously, 41 this may be a function of the age of our sample; many older individuals refrain from the use of ethanol for a variety of reasons, including its contraindication in the setting of numerous medications; as a result, alcohol consumption diminishes with age.…”
Section: Discussionmentioning
confidence: 86%
“…However, they found higher blood lead levels in patients with ET [9]. This group also reported similar current average consumption of ethanol in ET and controls [11] and increased levels of harmane and harmine (β-carboline alkaloids) in patients with ET [12]. More recently, they have found similar serum concentrations of 6 types of organochlorine pesticides and no differences in past occupational exposure to these toxins in 136 ET patients and 144 control subjects [13].…”
Section: Discussionmentioning
confidence: 89%
“…Although it has been suggested that some environmental factors could play a role in the risk for ET [3, 5,22,23,24,25,26,27,28], a reported family history is frequently associated with this disease [1,2,3]. To date, reports on the possible role of genetic polymorphisms in the risk for ET are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities of CYP polymorphisms should theoretically contribute to increasing the susceptibility to development of ET in patients exposed to some environmental factors that, according to current studies, could also be associated with the risk for this disease [3, 5,22,23,24,25,26,27,28]. In summary, our results suggest that heterozygosis for CYP2C19 * 1/CYP2C19 * 2 is associated with the risk for ET, although it does not have influence on the age at onset of the tremor, the presentation of acute side effects of primidone, or the existence of head, voice, tongue or chin tremor.…”
Section: Discussionmentioning
confidence: 99%